RELIGIOUS DIALOGUE AS A KEY TO INTERETHNIC COOPERATION IN BOSNIA AND HERZEGOVINA (Религиски дијалог и соработка, 2025)
Bosnia and Herzegovina is a country characterized by the interconnectedness of ethnicand religious affiliation, the country is home to three main ethnic groups (Serbs, Croats andBosnians) who are members of three different religions (Orthodoxy, Catholicism and Islam). Thehistory of Bosnia and Herzegovina is accompanied by deep religious and ethnic divisions and aspirations.The cause of conflict and intolerance in the country is often because of the different interestbetween all three religious parties. The intention of the authors of this paper is to draw attentionto the importance of religious dialogue in interethnic relations in Bosnia and Herzegovina, as themain key for spreading a culture of peace, mutual tolerance and understanding.